A modified polyacrylonitrile-based carbon felt and its modification method and application

By growing transition metal ion-doped g-C3N4 nanotubes in situ on polyacrylonitrile-based carbon felt, the problems of poor wettability, low specific surface area and few active sites were solved, and the performance of the flow battery was significantly improved.

CN116676775BActive Publication Date: 2025-04-15SICHUAN DEV XINGXIN VANADIUM ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310684801.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-04-15
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Polyacrylonitrile-based carbon felts have problems such as poor wetting, low specific surface area and few active sites in liquid flow batteries, which affect battery performance.

Method used

Improves its surface microstructure and electrochemical properties by growing transition metal ion-doped g-C3N4 nanotubes in situ on polyacrylonitrile-based carbon felt. The method includes steps such as roughening treatment, treatment of melamine solution and transition metal salt solution, drying and heat treatment.

Benefits of technology

It significantly improves the wetting properties, specific surface area and electrochemical activity of polyacrylonitrile-based carbon felt, and improves the performance of the flow battery, including the improvement of energy efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116676775B_ABST
    Figure CN116676775B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified polyacrylonitrile-based carbon felt and its modification method and application. First, the surface of the carbon felt is made rougher by acid treatment to facilitate the attachment of the precursor to its surface. Then, melamine is hydrolyzed by nitric acid to produce a white flocculent precursor on the surface of the polyacrylonitrile-based carbon felt. Then, the precursor is converted into g-C by high temperature treatment. 3 N 4 The present invention regulates the transition metal ion doping g‑C on the surface of the carbon felt by regulating the concentration of melamine, transition metal ions, and nitric acid, and the heating rate and heating temperature during the heating treatment. 3 N 4 The microscopic morphology and electrochemical properties of nanotubes provide new ideas for the modification of polyacrylonitrile-based carbon felt for liquid flow batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries, and in particular relates to a modified polyacrylonitrile-based carbon felt and a modification method and application thereof. Background Art

[0002] In recent years, due to people's continued concern about the energy crisis and global warming, the use of renewable energy such as solar energy, wind energy and tidal energy has steadily increased, and its share in the national energy structure has also increased. However, renewable energy has the disadvantages of intermittent and volatile, and the electricity it generates cannot be directly integrated into the power grid. The most effective way to solve this problem is to store the electricity and then release it. Therefore, a safe and reliable charging and discharging energy storage system is particularly important for the application of renewable energy.

[0003] Liquid flow batteries have attracted widespread attention due to their excellent energy storage performance. They have many advantages, such as high safety, low environmental load, flexible design, long service life, deep charging and discharging, and independent energy storage capacity and output power. They are suitable as a charging and discharging energy storage system.

[0004] After decades of development, flow batteries have made great progress. The current mainstream flow battery electrodes are carbon electrodes, among which polyacrylonitrile-based carbon felt has been widely used due to its good conductivity and corrosion resistance. However, polyacrylonitrile-based carbon felt also has disadvantages such as poor wettability, low specific surface area, and few active sites. Therefore, it is particularly important to explore an effective modification method for polyacrylonitrile-based carbon felt to improve the performance of flow batteries. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a modified polyacrylonitrile-based carbon felt and a modification method and application thereof, so as to solve the problems of poor wettability, low specific surface area and few active sites of the current polyacrylonitrile-based carbon felt.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is to provide a method for modifying polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC 3 N 4 The modification of nanotubes comprises the following steps:

[0007] S1: roughening treatment of polyacrylonitrile-based carbon felt;

[0008] S2: dissolving melamine in a solvent to obtain a melamine solution; dissolving a soluble transition metal salt in a nitric acid solution to obtain a salt solution;

[0009] S3: immersing the roughened polyacrylonitrile-based carbon felt in a melamine solution, and then adding a salt solution under stirring until the white flocs on the surface of the polyacrylonitrile-based carbon felt no longer increase;

[0010] S4: Dry the polyacrylonitrile-based carbon felt treated in S3, and then heat-treat it in an inert atmosphere to obtain gC with transition metal ions doped in situ on the surface. 3 N 4 Nanotube polyacrylonitrile-based carbon felt; the heat treatment is performed at a heating temperature of 300 to 550° C. for 2 to 10 hours, and a heating rate of 2 to 20° C. / min.

[0011] The beneficial effects of the technical solution of the present invention are as follows: firstly, the surface of the polyacrylonitrile-based carbon felt is roughened to facilitate the attachment of the precursor on the surface; then, melamine is hydrolyzed by nitric acid to produce a white flocculent precursor on the surface of the polyacrylonitrile-based carbon felt; and then, the precursor is converted into gC by high temperature treatment. 3 N 4 Nanotubes, thereby changing the microstructure of the carbon felt fiber surface and increasing the specific surface area of ​​the carbon felt. On the other hand, transition metal ions are doped into gC 3 N 4 The electronic structure of nanotubes is regulated in the nanotube structure, which improves the electrochemical performance of nanotubes. In addition, transition metal ions and gC 3 N 4 The rich N atoms in the carbon felt provide more active sites for the adsorption and conversion of electrochemically active substances during the charge and discharge process of the flow battery, thus promoting the electrochemical reaction. The present invention regulates the transition metal ion doping gC on the surface of the carbon felt by regulating the concentration of melamine, transition metal ions, and nitric acid, the heating rate and the heating temperature during the heating treatment. 3 N 4 The microscopic morphology and electrochemical properties of nanotubes provide new ideas for the modification of polyacrylonitrile-based carbon felt for liquid flow batteries.

[0012] Based on the above technical solution, the present invention can also be improved as follows.

[0013] Furthermore, the roughening treatment includes the following steps: immersing the polyacrylonitrile-based carbon felt in concentrated acid, keeping it warm at 60-200°C for 100-2000 minutes, then eluting it with water until the eluent is neutral, and then drying it at 60-100°C to constant weight.

[0014] Furthermore, the concentrated acid is concentrated nitric acid or concentrated sulfuric acid, and their concentrations are both 60-70 wt.%.

[0015] Furthermore, the solvent is ethylene glycol, the concentration of melamine in the melamine solution is 0.01-0.1 g / mL; the concentration of the soluble transition metal salt in the salt solution is 0.001-0.1 g / mL, and the concentration of nitric acid is 0.05-0.5M.

[0016] Furthermore, the soluble transition metal salt is an iron salt, a cobalt salt or a nickel salt.

[0017] Furthermore, the soluble transition metal salt is cobalt nitrate, cobalt chloride, nickel nitrate, nickel chloride, ferric nitrate or ferric chloride.

[0018] Furthermore, the drying process of the polyacrylonitrile-based carbon felt in S4 is: drying at 60-100° C. for 1-5 hours.

[0019] Furthermore, the inert atmosphere is an argon atmosphere or a nitrogen atmosphere, and the gas flow rate of the inert atmosphere is 20 to 100 mL / min.

[0020] The invention also discloses modified polyacrylonitrile-based carbon felt prepared by the modification method.

[0021] The present invention also discloses the use of modified polyacrylonitrile-based carbon felt in the preparation of liquid flow batteries, and the liquid flow batteries include but are not limited to all-vanadium, iron-chromium, all-iron, titanium-manganese, sodium polysulfide / bromine or organic system liquid flow batteries.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention in situ grows transition metal ion-doped gC with different microstructures on the surface of polyacrylonitrile-based carbon felt by regulating the concentrations of melamine, transition metal ions, and nitric acid, as well as the heating rate and heating temperature during the heating treatment. 3 N 4 Nanotubes, the effects of different process parameters on gC 3 N 4 Effect of nanotube microstructure.

[0024] 2. Transition metal ion-doped gC prepared by the present invention 3 N 4 Nanotube-modified polyacrylonitrile-based carbon felt was assembled into a flow battery and found that gC 3 N 4 Compared with unmodified carbon felt, the wettability, specific surface area and electrochemical activity of nanotube polyacrylonitrile-based carbon felt are significantly improved, which can effectively improve the performance of liquid flow batteries.

[0025] 3. Transition metal ion-doped gC prepared by the present invention 3 N 4 Nanotube-modified polyacrylonitrile-based carbon felt experimental materials are widely available, inexpensive, and experimental conditions are easy to meet. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a microstructure diagram of the modified polyacrylonitrile-based carbon felt in Example 1. DETAILED DESCRIPTION

[0027] In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the features and advantages of the present invention, rather than for limiting the claims of the present invention.

[0028] The experimental materials used in the present invention include: polyacrylonitrile-based carbon felt, melamine, ethylene glycol, concentrated nitric acid, concentrated sulfuric acid, ferric nitrate, cobalt nitrate, nickel nitrate, ferric chloride, cobalt chloride, nickel chloride, deionized water, argon (volume purity above 99.99%), and nitrogen (volume purity above 99.99%). All the materials used are conventional materials that can be purchased on the market.

[0029] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0030] Example 1

[0031] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0032] (1) 60 mL of concentrated nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm of polyacrylonitrile-based carbon felt was placed into the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 150°C for 12 h.

[0033] (2) taking out the carbon felt after the temperature immersion treatment in step (1), and rinsing it with deionized water until the pH of the rinsing solution is close to 7; then placing the rinsed carbon felt in an oven and drying it at 60° C. to constant weight.

[0034] (3) Weigh 3 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0035] (4) 2 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. Then 1 g of cobalt nitrate was weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the cobalt nitrate to obtain a salt solution.

[0036] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0037] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 60°C for 3 hours; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 450°C for 4 hours at a heating rate of 10°C / min; the inert atmosphere is argon gas with a volume purity of more than 99.99% and a gas flow rate of 30 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0038] The modified polyacrylonitrile-based carbon felt prepared in this embodiment is as follows: Figure 1 As shown, transition metal ion doped gC 3 N 4 Nanotubes have a significantly increased specific surface area and more active sites. When assembled into an all-vanadium liquid flow battery, the current density is 150mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 66.1% to 72.5% compared with the unmodified carbon felt.

[0039] Example 2

[0040] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0041] (1) 60 mL of concentrated sulfuric acid (60 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm of polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the carbon felt was completely immersed in concentrated nitric acid. The hydrothermal reactor was then placed in an oven and kept warm at 60°C for 24 h.

[0042] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 80° C. to constant weight.

[0043] (3) Weigh 2 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0044] (4) 2 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. 0.5 g of nickel nitrate was then weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the nickel nitrate to obtain a salt solution.

[0045] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0046] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 60°C for 3 hours; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 350°C for 5 hours at a heating rate of 5°C / min; the inert atmosphere is argon gas with a volume purity of more than 99.99% and a gas flow rate of 30 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0047] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have significantly increased specific surface area and more active sites. When assembled into an iron-chromium flow battery, the current density is 100 mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 70.3% to 75.5% compared with the unmodified carbon felt.

[0048] Example 3

[0049] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0050] (1) 60 mL of concentrated sulfuric nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 100°C for 16 h.

[0051] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 60° C. to constant weight.

[0052] (3) Weigh 5 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0053] (4) 2 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. 1.5 g of ferric nitrate was then weighed and added to the diluted nitric acid aqueous solution. The mixture was stirred continuously to fully dissolve the ferric nitrate to obtain a salt solution.

[0054] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0055] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 80°C for 1 hour; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 550°C for 6 hours at a heating rate of 10°C / min; the inert atmosphere is nitrogen with a volume purity of more than 99.99% and a gas flow rate of 30 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0056] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have a significantly increased specific surface area and more active sites. When assembled into titanium-manganese flow batteries, the current density is 70 mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 61.3% to 65.4% compared with the unmodified carbon felt.

[0057] Example 4

[0058] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0059] (1) 60 mL of concentrated sulfuric nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 200°C for 8 h.

[0060] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 100° C. to constant weight.

[0061] (3) Weigh 4 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0062] (4) 3 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. 0.5 g of cobalt nitrate was then weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the cobalt nitrate to obtain a salt solution.

[0063] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0064] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 100°C for 1 hour; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 500°C for 8 hours at a heating rate of 10°C / min; the inert atmosphere is argon gas with a volume purity of more than 99.99% and a gas flow rate of 30 mL / min; after the heat treatment, modified polyacrylonitrile-based carbon felt can be obtained.

[0065] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have a significantly increased specific surface area and more active sites. When assembled into a zinc-iron flow battery, the current density is 100 mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 64.5% to 67.8% compared with the unmodified carbon felt.

[0066] Example 5

[0067] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0068] (1) 60 mL of concentrated sulfuric nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 150°C for 12 h.

[0069] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 60° C. to constant weight.

[0070] (3) Weigh 4 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0071] (4) 4 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. 0.6 g of cobalt chloride was then weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the cobalt chloride to obtain a salt solution.

[0072] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0073] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 60°C for 5 hours; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 450°C for 3 hours at a heating rate of 10°C / min; the inert atmosphere is nitrogen with a volume purity of more than 99.99% and a gas flow rate of 30 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0074] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have significantly increased specific surface area and more active sites. When assembled into zinc-bromine flow batteries, the current density is 50 mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 69.5% to 72.5% compared with the unmodified carbon felt.

[0075] Example 6

[0076] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0077] (1) 60 mL of concentrated sulfuric nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 150°C for 12 h.

[0078] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 60° C. to constant weight.

[0079] (3) Weigh 3 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0080] (4) 3 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. 1.5 g of nickel chloride was weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the nickel chloride to obtain a salt solution.

[0081] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0082] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 60°C for 4 hours; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 350°C for 7 hours at a heating rate of 20°C / min; the inert atmosphere is nitrogen with a volume purity of more than 99.99% and a gas flow rate of 20 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0083] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have significantly increased specific surface area and more active sites. When assembled into an all-vanadium liquid flow battery, the current density is 80 mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 60.7% to 64.3% compared with the unmodified carbon felt.

[0084] Example 7

[0085] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0086] (1) 60 mL of concentrated sulfuric nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 150°C for 12 h.

[0087] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 60° C. to constant weight.

[0088] (3) Weigh 3 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0089] (4) 4 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. Then 0.5 g of ferric chloride was weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the ferric chloride to obtain a salt solution.

[0090] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0091] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 60°C for 4 hours; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere at a temperature of 450°C for 8 hours at a heating rate of 15°C / min; the inert atmosphere is argon gas with a volume purity of more than 99.99% and a gas flow rate of 20 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0092] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have significantly increased specific surface area and more active sites. When assembled into sodium polysulfide / bromine flow batteries, the current density is 100mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 69.3% to 75.5% compared with the unmodified carbon felt.

[0093] Example 8

[0094] A modified polyacrylonitrile-based carbon felt, wherein the modification is to in-situ grow transition metal ion-doped gC on the polyacrylonitrile-based carbon felt. 3 N 4 Nanotubes are prepared by the following steps:

[0095] (1) 60 mL of concentrated sulfuric nitric acid (68 wt.%) was poured into a hydrothermal reactor with a volume of 100 mL, and then 3×3 cm polyacrylonitrile-based carbon felt was placed in the hydrothermal reactor, and the concentrated nitric acid was completely immersed in the carbon felt. Then, the hydrothermal reactor was placed in an oven and kept warm at 150°C for 12 h.

[0096] (2) The carbon felt after the heat preservation and immersion treatment in step (1) is taken out and rinsed with deionized water until the pH of the rinse liquid is close to 7; then the rinsed carbon felt is placed in an oven and dried at a temperature of 60° C. to constant weight.

[0097] (3) Weigh 4 g of melamine, add it to 100 mL of ethylene glycol, and stir mechanically until the drugs are mixed evenly to obtain a melamine solution.

[0098] (4) 2 mL of concentrated nitric acid (68 wt.%) was weighed and diluted to 300 mL with deionized water. 2 g of cobalt chloride was then weighed and added to the diluted nitric acid aqueous solution, and the mixture was stirred continuously to fully dissolve the cobalt chloride to obtain a salt solution.

[0099] (5) Immersing the carbon felt treated in step (2) in a melamine solution, and slowly adding a salt solution under stirring after being fully immersed until the amount of white flocs on the surface of the carbon felt stops increasing.

[0100] (6) The carbon felt obtained in step (5) is placed in an oven and dried at 60°C for 4 hours; the dried carbon felt is then placed in a tubular furnace and heat treated in an inert atmosphere, wherein the heat treatment is performed at a heating temperature of 500°C for 6 hours at a heating rate of 5°C / min; the inert atmosphere is argon gas with a volume purity of more than 99.99% and a gas flow rate of 30 mL / min; after the heat treatment, the modified polyacrylonitrile-based carbon felt can be obtained.

[0101] The modified polyacrylonitrile-based carbon felt prepared in this embodiment has a morphology and structure similar to that of the modified polyacrylonitrile-based carbon felt in Example 1, and transition metal ion-doped gC 3 N 4 Nanotubes have a significantly increased specific surface area and more active sites. When assembled into an all-iron flow battery, the current density is 75 mA / cm 2 Under the constant current charge and discharge test, the energy efficiency was increased from the original 63.7% to 68.4% compared with the unmodified carbon felt.

[0102] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for modifying polyacrylonitrile-based carbon felt, characterized in that: The modification is to in-situ grow transition metal ion-doped g-C3N4 nanotubes on polyacrylonitrile-based carbon felt, and the modification comprises the following steps: S1: roughening treatment of polyacrylonitrile-based carbon felt; S2: dissolving melamine in a solvent to obtain a melamine solution; dissolving a soluble transition metal salt in a nitric acid solution to obtain a salt solution; S3: immersing the roughened polyacrylonitrile-based carbon felt in a melamine solution, and then adding a salt solution under stirring until the white flocs on the surface of the polyacrylonitrile-based carbon felt no longer increase; S4: Dry the polyacrylonitrile-based carbon felt treated by S3, and then perform heat treatment in an inert atmosphere to obtain polyacrylonitrile-based carbon felt with g-C3N4 nanotubes doped with transition metal ions in situ grown on the surface; the heat treatment is performed by heating at a heating temperature of 300 to 550°C for 2 to 10 hours, and a heating rate of 2 to 20°C / min.

2. The modification method according to claim 1, characterized in that: The roughening treatment comprises the following steps: immersing the polyacrylonitrile-based carbon felt in concentrated acid, keeping it warm at 60-200° C. for 100-2000 minutes, then eluting it with water until the eluting liquid is neutral, and then drying it at 60-100° C. to constant weight.

3. The modification method according to claim 2, characterized in that: The concentrated acid is concentrated nitric acid or concentrated sulfuric acid, and their concentrations are both 60-70 wt.%.

4. The modification method according to claim 1, characterized in that: The solvent is ethylene glycol, the concentration of melamine in the melamine solution is 0.01-0.1 g / mL; the concentration of soluble transition metal salt in the salt solution is 0.001-0.1 g / mL, and the concentration of nitric acid is 0.05-0.5M.

5. The modification method according to claim 1 or 4, characterized in that: The soluble transition metal salt is an iron salt, a cobalt salt or a nickel salt.

6. The modification method according to claim 5, characterized in that: The soluble transition metal salt is cobalt nitrate, cobalt chloride, nickel nitrate, nickel chloride, ferric nitrate or ferric chloride.

7. The modification method according to claim 1, characterized in that: The drying process of the polyacrylonitrile-based carbon felt in S4 is: drying at 60-100°C for 1-5 hours.

8. The modification method according to claim 1, characterized in that: The inert atmosphere is an argon atmosphere or a nitrogen atmosphere, and the gas flow rate of the inert atmosphere is 20 to 100 mL / min.

9. Modified polyacrylonitrile-based carbon felt obtained by the modification method according to any one of claims 1 to 8.

10. Use of the modified polyacrylonitrile-based carbon felt according to claim 9 in the preparation of liquid flow batteries.

Citation Information

Patent Citations

  • Novel photocatalytic material and dual-photocatalytic electrode self-biasing pollution control system

    CN107952464A

  • Preparation method of iron-ion-doped carbon nitride nanotube and obtained product

    CN108339562A